New types of general consent in telehealth application usage - Mohd Saad N.; Alias R.A. (2023)
Consent type is divided into four types, namely general consent, general consent with specific denial, general denial with specific consent and general denial. However, in the new information age, general consent is no longer appropriate because it allows anyone to access information. Thus, new types of general consent need to be identified. This investigation looks into (1) level of illness, and (2) patient's willingness to give consent. General consent can be subcategorized into three new types, namely (1) one-time consent, (2) episodic consent, and (3) periodic consent. The integration of all three types provides a secured environment and higher level of trust between patients and physicians/doctors and also between patients and health institutions. 2012 IEEE.